CBDC next-level: A new architecture for financial "super-stability" - Biagio Bossone; Michael R. Haines (Levy Economics Institute of Bard College, 2023)
Fractional reserve regimes generate fragile banking, and full reserve regimes (e.g., narrow banking) remove fragility at the cost of suppressing the role of banks as lenders. A Central Bank Digital Currency (CBDC) could provide safe money, but at the cost of potentially disrupting bank lending. Our aim is to avoid this potential disruption. Building on the recent literature on CBDCs, in this study we propose what we call the "CBDC next-level model," whereby the central bank creates money by lending to banks, and banks on-lend the proceeds to the economy. The proposed model would allow for deposits to be taken off the balance sheet of banks and into the balance sheet of the central bank, thereby removing significant risk from the banking system without adversely impacting banks' basic business. Once CBDC is injected in the system, irrespective of however it is used, wherever it accumulates, and whoever holds and uses it, it will always represent central bank equity, and no losses or defaults by individual banks or borrowers can ever dent it or weaken the central bank's capital position or hurt depositors. Yet, individual borrowers and banks would still be required to honor their debt in full, lest they would be bound to exit the market or even be forced into bankruptcy. The CBDC next-level model solution would eliminate the threat of bank runs and system collapse and induce a degree of financial stability ("super-stability") that would be unparalleled by any existing banking system.
Keywords: E42; E51; G01; G21; G23; G33; 330; Bank Deposits and Loans; Bankruptcy; Central vs Commercial Bank Money; Fractional vs Full Reserves Regime; Money Creation; Payment Service Provider; Seigniorage; Stability; Central Bank Digital Currency; Digital Currency; CBDC; Monetary Policy